RETROSPECTIVE ANALYSIS OF GENDER-AGE STRUCTURE AND COMORBID PATHOLOGY OF PATIENTS WITH VIRAL AND BACTERIAL PNEUMONIA ASSOCIATED WITH COVID-19 - Romanyuk, L. B.; Volch, I. R.; Kravets, N. Y.; Pyatkovskyy, T. I.; Zahrychuk, O. M. (International Journal of Medicine and Medical Research, 2022)
Background. In December 2019 first case of COVID-19 was first registered in Wuhan, Hubei province, China. This infectious disease primarily causes respiratory tract infection, but can also affect the other organs and systems. Objective. In this study, the features of the gender-age structure and comorbid pathology of the patients with viral and bacterial pneumonia who were treated in inpatient department in the period from September to December 2020 are summarized. Methods. The research was conducted in Ternopil Municipal Hospital No. 3, Ternopil, Ukraine. Clinical cases of 262 patients with viral and bacterial pneumonia associated with COVID-19 were studied retrospectively. Results. Both men and women has been affected by this pathology in Ternopil region with the same frequency in contrast with the established fact that men are less resistant to infections that women. Most of the patients ranged in age from 51 to 70 years, however, a fair number of patients were over the age of 70 years. Concomitant pathology was diagnosed in 65.5% of the patients with coronavirus infection. Coronary heart disease (34.5%) is leading in the structure of comorbid conditions. Conclusions. During the COVID-19 pandemic, timely diagnosis and medical care of the patients over 50 years of age is of great importance. The analysis of concomitant pathology proves that the people with cardiovascular pathology are in the increased risk group.